Kajian Pustaka tentang Fenomena Perubahan Makna dalam Bahasa Arab: Perluasan, Penyempitan, dan Pergeseran - Ferdiyana, Ferdiyana; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study is a library research aimed at analyzing the phenomenon of semantic change (extension, narrowing, and shift) in the Arabic language based on both classical and modern theories. The primary source of this research is Tam?m ?assan’s Al-Lughah al-?Arabiyyah: Ma?n?h? wa Mabn?h?, which emphasizes the interrelation between form (mabn?) and meaning (ma?n?) within the structure of Arabic. The findings indicate that semantic change arises not only from internal linguistic processes but is also influenced by socio-cultural, psychological, religious-historical, as well as scientific and technological factors. The implementation of these phenomena can be observed in Qur’anic exegesis and Hadith studies, the compilation of modern dictionaries, digital communication, and contemporary Arabic language teaching. Thus, semantic change reflects the vitality and adaptive capacity of Arabic in responding to the dynamics of time without losing its semantic and historical roots.